ChemInform Abstract: Nanostructured Mg‐Al Hydrotalcite as Catalyst for Fine Chemical Synthesis. Issue 33 (19th August 2014) - Basahel, Sulaiman N.; Al‐Thabaiti, Shaeel A.; Narasimharao, Katabathini; Ahmed, Nesreen S.; Mokhtar, Mohamed
Abstract Review: 170 refs.